Lived Experiences of Married Postgraduate Students at University of Zambia Regarding Marriage Mate Selection - , Masauso Chirwa, Lister Banda, Kusanthan Thankian (Archives of Current Research International, 2022)
This research sought to find out the lived experiences of married postgraduate students at UNZA regarding marriage mate selection. The study used a qualitative research methodology as well as a Case Study as its research design towards data collection. The data was collected using a semi-structured interview guided questions. The sample selection was 16 in total of postgraduate students at UNZA which included 8 males and 8 female participants. The general literature overview of this research indicated that marriage is a fundamental social institution that exists throughout the world. And that marriage mate selection is one of the most important decisions of people’s social life which determines their happiness in marriage. However, the findings in this study revealed that people looked for attributes or factors such as education in marriage mate selection because they believed that marrying a fellow educated person made it easy to relate as their thinking would be aligned to theirs. Secondly the financial stability of a potential marriage partner was also an important attribute that both males and females looked for in their prospective mate. Thirdly the study showed that a God-fearing partner was preferred unlike a non-believer because of the belief that Godly people were less likely to indulge in unholy conduct such as infidelity. The other perspectives includes some female preference of a man who is tall in height and dark in complexion, while some men preferred women who are beautiful with small and curvy body structure. Finally, the overall attributes in marriage mate selection included a man who is loving, caring and with good leadership qualities, while males preferred a woman who is respectful, intelligent, trustworthy, understanding and one who refrained from taking alcohol. For further studies, it is recommended that other research focus should be conducted in communities where there are less educated males and females.